BERA in the detection of hearing loss in high risk children: an observational study in two tertiary care teaching hospitals in upper Assam region - Mili, M. K.; Sarma, Debajit; Sarmah, Monikuntal; Goswami, Suhanee; Pegu, Krisna; Talukdar, Linkan; Talukdar, Sharmistha; Siddique , Mohsina (International Journal of Research in Medical Sciences, 2023)
Background: Significant hearing loss affects children globally (1-3/1,000 infants at birth). Early diagnosis (<6 months age) and subsequent early intervention facilitates normal development of language, regardless of the severity of hearing loss. Methods: A hospital-based, descriptive, retrospective study was done in two tertiary-care centres of Upper Assam region, upon total (55 + 46 =) 101 high risk children (<15 years) during a study period of 1 year. Patients were subjected to a questionnaire, and hearing tests (BERA/OAE) were performed. Results: Majority of the cases were <5 years of age, with male preponderance (66.30% cases). NICU graduates with history of ototoxic medications/mechanical ventilation, neonatal hyperbilirubinemia and caregiver concern were the common presenting risk factors identified. Conclusions: 49.50% cases (n=50) suffered from hearing loss [most common was severe degree of hearing loss, n= 24]. 75% cases in AMCH and 63.6% in LMCH with caregiver concern, 55.55% cases in AMCH and 50% in LMCH with past neonatal hyperbilirubinemia; 50% cases with positive family history; and 46.66% NICU graduates tested positive for hearing loss. Ideally, all high risk children <15 years should be screened for hearing loss with earliest intervention and rehabilitation, to enable them to lead a normal life and reduce the burden of handicap in the community.